Salinity Stress Induces Phase Separation of Plant BARENTSZ to Form Condensates - Peigang Li; Lanfeng Wu; Wenchao He; Shanshan Zhang; Chaoying He (Rice)
Abstract Phase separation (PS) of BARENTSZ (BTZ), a core member of the exon-junction complex (EJC), is involved in various physiological and developmental processes in animals. However, less is known about plant equivalents. Here, we demonstrated that the loss of function of Oryza sativa BTZ genes (OsBTZs) reduced rice tolerance to salinity stress. Moreover, OsBTZ proteins underwent PS independent of other core members of EJC, forming condensates under salt stress. OsBTZs may recruit proteins that play roles in the salt tolerance response to form cytoplasmic condensates, which act as stress granules. The predicted prion-like domain (PrLD), that originated ancestrally and is functionally conserved, was demonstrated to be key to the PS of OsBTZs upon NaCl treatment. This work revealed a new role for plant BTZs through an evolutionarily conserved mechanism—PS—in the formation of condensates in response to salinity stress, thus providing new insights into the adaptive evolution of plant BTZs under abiotic stress.